Effect of bamboo fiber aspect ratio on the bending properties of bamboo fiber/polypropylene composite. Issue 1 (27th July 2022) - Yu, Weipeng; Zhang, Wei; Zhi, Bo; Yao, Wenbin; Fujii, Toru
Abstract: Aspect ratio is a critical parameter of bamboo fiber (BF), and is not well defined for the bending properties of BF composite for automobile inner parts. In this study, six different types of BF were extracted and tensile tested that 20–130 mm in length and 483–713 in aspect ratio, then mixed with polypropylene (PP) fiber which has been added 5%wt maleic anhydride grafted polypropylene by non-fabric and heat pressing technology. The results present that the bending performance of BF composite is the best when the BF aspect ratio is 600–700; and the modified Halpin–Tsai equation with anisotropic material factor can approximate fitting out the relationship between BF aspect ratio and bending modulus of BF/PP composite. Polyvinyl alcohol can effectively enhance the three dimensional (3D) cross structure of non-fabric mats showed by optical microscopy images, so as improve the bending modulus of 12%.